Bioactivities of triazolium-based N-heterocyclic carbene salts - Song, Jia (2023)
1,2,4-Triazolium salts are precursors of N-heterocyclic carbenes (NHCs), which have been extensively used as effective catalysts and ligands for both asymmetric and non-enantioselective reactions. Nevertheless, they are also a kind of quaternary ammonium compounds (QACs) that possess amphipathic properties. The unique chemical and physical properties of 1,2,4-triazolium salts have received significant attention from scientists focusing on the development of novel bioactive molecules as pesticides and medicines. It is timely and meaningful to summarize the bioactivities of 1,2,4-triazolium salt derivatives against various bacteria, fungi, cancer cells, and other pathogens in the past 30 years. Meanwhile, the structure-activity relationship (SAR) of 1,2,4-triazolium salts was also summarized. Finally, our perspective on the future development and applications of triazolium salts as agrichemicals or human drugs is presented.